Rozłóż na czynniki:
a) 6a + 3a² - 2b - ab
b) 21x + 7x² - xy - 3y
c) q² - p²q - 3pq + 3p³
d) x²y + y³ +2xy² + 3x³
e) 14r² + 21r - 2rs - 3s

Przedstaw jako sumę:
a) (2x - 3y)³
b) (2x + ½)²
c) (x - 2y)(x² + 2xy + 2y²)
d) (x + ½y)(x² + xy + y²)

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-10-22T23:15:09+02:00
Rozłóż na czynniki:
a) 6a + 3a² - 2b - ab = 3a(2 + a) - b (2 + a) = (3a - b)(2 + a)

b) 21x + 7x² - xy - 3y = 7x (3 + x) - y (x + 3) = (x + 3)(7x - y)

c) q² - p²q - 3pq + 3p³ = q (q - p²) - 3p (q - p²) = (q - 3p) (q - p²)

d) x²y + y³ +2xy² + 3x³ =

e) 14r² + 21r - 2rs - 3s = 7 r (2r + 3) - s (2r + 3) = (7r - s)(2r + 3)

Przedstaw jako sumę:
a) (2x - 3y)³ = (2x)³ - 3 * (2x)² * (3y) + 3 * (2x) * (3y)² - (3y)³ = 8x³ +(- 36 x² y) + 54 x y² + (- 27 y³)

b) (2x + ½)² = 4x² + 2x + 1/4

c) (x - 2y)(x² + 2xy + 2y²) = x³ + 2x²y + 2xy² - 2x²y - 4xy² - 4y³ = x³ + 2xy² +(- 4xy²) + (- 4y³)

d) (x + ½y)(x² + xy + y²) =x³ + 3/2 x²y + 3/2 xy² + 1/2 y³